"Frozen conflicts" in Europe - Bebler, Anton (Verlag Barbara Budrich, 2015)
Oft forgotten but simmering "frozen conflicts" continuously mark the political map of Europe. All located in South Eastern Europe, the Black Sea area and Transcaucasia, these conflicts run along ethnic, national, cultural and linguistic lines, separating communities. This insightful book offers a rare critical analyses of the cases of Northern Cyprus, Transnistria, Abkhazia, South Ossetia, Nagorno-Karabakh, Kosovo, and Crimea.